Neuroimaging of rapid eye movement sleep behavior disorder - Bourouin, P; Rahayel, S; Gaubert, M; Hu, M; Gagnon, J (Elsevier, 2019)
Idiopathic rapid eye movement sleep behavior disorder (iRBD) is a parasomnia characterized by the loss of muscle atonia and the presence of undesirable motor manifestations during rapid eye movement sleep. Research findings have shown that iRBD is a prodromal stage of synucleinopathies such as Parkinson's disease, dementia with Lewy bodies, and multiple system atrophy. A wide array of neuroimaging techniques have improved our understanding of the prodromal stage of these diseases in patients with iRBD, and identified potential biomarkers. In this chapter, we summarize current knowledge about functional and structural central and peripheral neuroimaging in iRBD, including cross-sectional and longitudinal studies using positron emission tomography, single-photon emission computed tomography, magnetic resonance imaging, and transcranial sonography. Current neuroimaging research has revealed several brain alterations in iRBD similar to those reported in synucleinopathies, thereby improving our understanding of the pathophysiology underlying the clinical presentation and progression of their prodromal stages. Moreover, some abnormalities detected by neuroimaging show promise as potential biomarkers to predict which individuals with iRBD may be at risk of conversion and therefore candidates for inclusion in future clinical trials of neuroprotection.